NUEVAS ESPECIES DE COLLETIDOS CHILENOS (HYMENOPTERA: COLLETIDAE) - Rojas, M.; Toro G., H. (Acta Entomológica Chilena, 2022)
This paper presents the description of four new species of Colletes with metallic blue-green metasoma. The eight species of chilean Colletes with this characteristic are keyed. The new species are: chusmiza, guanta, quelu y vicugnensis.